2019
DOI: 10.1108/et-10-2017-0148
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education and undergraduate students’ self- and paid-employment intentions

Abstract: Purpose The purpose of this paper is to conceptually explore the relationship between Entrepreneurship Education (EE) and undergraduate students’ self- and paid-employment intentions. Specifically, the paper aims to examine the effect of paid-employment intention on the relationship between EE and self-employment intention. Design/methodology/approach This paper reviewed extensively related literature on EE, entrepreneurial intentions and the theory of planned behaviour (TPB). The detailed literature review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 69 publications
4
46
0
1
Order By: Relevance
“…So how can we increase the number of entrepreneurs? Some scholars believe that entrepreneurs can be created by cultivating entrepreneurial qualities such as entrepreneurial knowledge, attitudes, and skills through education and encouragement of creativity (Otache, 2019 ). Public policy planners and government agencies worldwide recognized entrepreneurship education as a means to encourage social innovation (Jones and Iredale, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…So how can we increase the number of entrepreneurs? Some scholars believe that entrepreneurs can be created by cultivating entrepreneurial qualities such as entrepreneurial knowledge, attitudes, and skills through education and encouragement of creativity (Otache, 2019 ). Public policy planners and government agencies worldwide recognized entrepreneurship education as a means to encourage social innovation (Jones and Iredale, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…We acknowledge that entrepreneurship education and other entrepreneurial activities take place in the HEIs of many countries and that, in many cases, participation in entrepreneurship courses is a mandatory requirement for graduation. However, previous studies have questioned the ability of entrepreneurship courses and initiatives promoted by higher education to enhance students' entrepreneurial aspirations and intentions (Otache, 2019). For example, Støren (2014) found that, among Norwegian graduates, those who had studied entrepreneurship-related courses as F o r P e e r R e v i e w part of their curriculum had no greater intentions to start their own business than other graduates.…”
Section: Job Creation Intentionmentioning
confidence: 99%
“…In Nigeria, for instance, 40 per cent of the total population, or almost 83 million people, live below the country's poverty line of 137,430 Naira ($381.75) per year and do not have a job to earn a livelihood (World Bank (2019). This situation has led to the Nigerian government's policy on promoting entrepreneurship or small business start-up as a means of reducing poverty, creating more jobs and helping people to improve their living standard (e.g., Otache, 2019). Furthermore, the drive for HEIs to engage or partner with industry in the effort to produce competent graduates who can start their own businesses and create jobs has attracted many researchers in recent years.…”
mentioning
confidence: 99%
“…It is also an important part of career-related tasks, such as the entrepreneurial process, as it prompts an individual's choice, determination, and perseverance (Al-Mamun et al, 2016). Thus, self-employment is concerned with an individual's decision on what to be done with the skills they possess, not just with the skills individual experienced (Otache, 2019). The greater the individual's self-employment inclination, the more confident he/she is to be successful in a particular task domain (Otache, 2019).…”
Section: Literature Review and Hypotheses Development Entrepreneurialmentioning
confidence: 99%
“…Thus, self-employment is concerned with an individual's decision on what to be done with the skills they possess, not just with the skills individual experienced (Otache, 2019). The greater the individual's self-employment inclination, the more confident he/she is to be successful in a particular task domain (Otache, 2019). Several studies have established that Entrepreneurial Self-Employment is a strong driver of entrepreneurial behavior (Al-Mamun et al, 2016; Otache, 2019) and anticipated to affect individual choices, goals, effort, emotional responses, ability to cope, and perseverance (Gelaidan & Abdullateef, 2017; Al-Mamun et al, 2017; Odewale et al, 2019).…”
Section: Literature Review and Hypotheses Development Entrepreneurialmentioning
confidence: 99%